Tingkat Aktivitas Sel Endokrin Penghasil Folikel Stimulating Hormon (FSH) Terkait Pemberian Pasak Bumi (Eurycoma Longifolia JACK) - Pratomo, Hurip; Supriatna, Iman; Winarto, Adi; Manalu, Wasmen (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2012)
Pasak bumi is popular as an aphrodisiac. Traditionally, pasak bumi infusion is used to increase libido and duration of erection. The research was focused on: Activity level of FSH cells after three days of pasak bumi treatment. The research was carried out by evaluation using immunohistochemistry method via antibody anti FSH staining. The result of the research showed that a dosage of 18 mg/200 g body weight (bw) orally of pasak bumi maintained certain endoceine positive cells e.g. FSH production cells and were found stabile in the third days. Pasak bumi serves a stabilizer for intracellular levels of FSH in the anterior hipophysis/pituatary.